(3+i)(6-2i)=

Simple and best practice solution for (3+i)(6-2i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3+i)(6-2i)= equation:


Simplifying
(3 + i)(6 + -2i) = 0

Multiply (3 + i) * (6 + -2i)
(3(6 + -2i) + i(6 + -2i)) = 0
((6 * 3 + -2i * 3) + i(6 + -2i)) = 0
((18 + -6i) + i(6 + -2i)) = 0
(18 + -6i + (6 * i + -2i * i)) = 0
(18 + -6i + (6i + -2i2)) = 0

Combine like terms: -6i + 6i = 0
(18 + 0 + -2i2) = 0
(18 + -2i2) = 0

Solving
18 + -2i2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -2i2 = 0 + -18

Combine like terms: 18 + -18 = 0
0 + -2i2 = 0 + -18
-2i2 = 0 + -18

Combine like terms: 0 + -18 = -18
-2i2 = -18

Divide each side by '-2'.
i2 = 9

Simplifying
i2 = 9

Take the square root of each side:
i = {-3, 3}

See similar equations:

| 4v-4=-8 | | 45x-12=80 | | N-6.5=15 | | x^2+32x+130=0 | | 3x^2+6x^2y-9x^2z= | | (2x-7)(x+4)=33856 | | -14n=42 | | 2x+5+7x+8x=107 | | 1/5w-4=-2 | | -2nb=-6z | | 25=-4c+97 | | 4(y-6)+14(y+10)= | | -a-2a=-24 | | K-17.8=-3 | | 6d=78 | | -17p=0102 | | 15-=y/7 | | x+(x+-38)=180 | | -2(r+4)=24 | | 3(a-4)+15=13 | | 12p=15 | | 4(x-6)+14(x+10)= | | 129=15 | | 240=(5*w*2)+(w*2) | | 89=0.9d+71 | | 408b=36 | | (3/10)*(5/3) | | 5(5x+7)-12x= | | 8.1=-7a+2.1 | | M-11=43 | | x^2+7+9=3 | | f(-4)=9x+8 |

Equations solver categories